Observed inequality in urban greenspace exposure in China. (November 2021) - Song, Yimeng; Chen, Bin; Ho, Hung Chak; Kwan, Mei-Po; Liu, Dong; Wang, Fei; Wang, Jionghua; Cai, Jixuan; Li, Xijing; Xu, Yong; He, Qingqing; Wang, Hongzhi; et al.
Highlights: Inequality in urban greenspace exposure is assessed for 303 cities in China. Dynamic inequality is characterized using multi-source geospatial data. Severe inequality in greenspace exposure is pervasive in Chinese cities. Dry cold climate and urban densification contribute to high inequality. Abstract: Given the important role of green environments playing in healthy cities, the inequality in urban greenspace exposure has aroused growing attentions. However, few comparative studies are available to quantify this phenomenon for cities with different population sizes across a country, especially for those in the developing world. Besides, commonly used inequality measures are always hindered by the conceptual simplification without accounting for human mobility in greenspace exposure assessments. To fill this knowledge gap, we leverage multi-source geospatial big data and a modified assessment framework to evaluate the inequality in urban greenspace exposure for 303 cities in China. Our findings reveal that the majority of Chinese cities are facing high inequality in greenspace exposure, with 207 cities having a Gini index larger than 0.6. Driven by the spatiotemporal variability of human distribution, the magnitude of inequality varies over different times of the day. We also find that exposure inequality is correlated with low greenspace provision with a statistical significance (p-value < 0.05). The inadequate provision may result from various factors, such as dry cold climate and urbanization patterns. Our study provides evidence and insights for central and local governments in China to implement more effective and sustainable greening programs adjusted to different local circumstances and incorporate the public participatory engagement to achieve a real balance between greenspace supply and demand for developing healthy cities.